The Impact of Cohort Size and Local Labor Market Conditions on Human Capital Accumulation in Europe - Torge Middendorf (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2007)
Recent studies emphasize the impact of macroeconomic factors on educational attainment. They show that although individual factors like the educational level of one's parents play a decisive role in determining the human capital accumulation of the children, the cohort size as well as the local labor market seem to have a significant impact, too. This paper analyzes the impact of birth cohort size as well as unemployment on educational attainment in Europe using the European Community Household Panel. Estimation results suggest that neither the size of the birth cohort nor the local unemployment rate induces a change in the individual's schooling decision.
Keywords: I21; J21; J62; 330; Educational attainment; demography; multivariate ordered probit; Bildungsniveau; Bildungsverhalten; Bevölkerung; Regionale Arbeitslosigkeit; Schätzung; EU-Staaten